Whole-exome sequencing identifies causative mutations in families with congenital anomalies of the kidney and urinary tract - Van Der Ven, Amelie T.; Connaughton, Dervla M.; Ityel, Hadas; Mann, Nina; Nakayama, Makiko; Chen, Jing; Vivante, Asaf; Hwang, Daw-Yang; Schulz, Julian; Braun, Daniela A.; Schmidt, Johanna Magdalena; Schapiro, David; et al. (Journal of the American Society of Nephrology, 2018)
Background Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of kidney disease in the first three decades of life. Previous gene panel studies showed monogenic causation in up to 12% of patients with CAKUT. Methods We applied whole-exome sequencing to analyze the genotypes of individuals from 232 families with CAKUT, evaluating for mutations in single genes known to cause human CAKUT and genes known to cause CAKUT in mice. In consanguineous or multiplex families, we additionally performed a search for novel monogenic causes of CAKUT. Results In 29 families (13%), we detected a causative mutation in a known gene for isolated or syndromic CAKUT that sufficiently explained the patient's CAKUT phenotype. In three families (1%), we detected a mutation in a gene reported to cause a phenocopy of CAKUT. In 15 of 155 families with isolated CAKUT, we detected deleterious mutations in syndromic CAKUT genes. Our additional search for novel monogenic causes of CAKUT in consanguineous and multiplex families revealed a potential single, novel monogenic CAKUT gene in 19 of 232 families (8%). Conclusions We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.
Created from Fastlane, Scopus look-up